Energy-storage properties and electrocaloric effects of Pb(1-3x/2)LaxZr0.85Ti0.15O3 antiferroelectric thick films - Zhao, Ye; Hao, Xihong; Zhang, Qi (American Chemical Society, 2014)
1-µm-Pb(1-3x/2)LaxZr0.85Ti0.15O3 (PLZT) antiferroelectric (AFE) thick films with x = 0.08, 0.10, 0.12, and 0.14 were deposited on LaNiO3/Si (100) substrates by a sol-gel method. The dielectric properties, energy-storage performance, electrocaloric effect, and leakage current behavior were investigated in detail. With increasing La content, dielectric constant and saturated polarizations of the thick films were gradually decreased. A maximum recoverable energy-storage density of 38 J/cm3 and efficiency of 71% were achieved in the thick films with x = 0.12 at room temperature. Moreover, a large reversible adiabatic temperature change ∆T = 25.0 o C was presented in the thick films with x = 0.08 at 127 o C at 990 kV/cm. All the samples had a lower leakage current density below 10- 6 A/cm2 at room temperature. These results indicated that the PLZT AFE thick films could be a potential candidate for applications in high energy-storage density capacitors and cooling devices.
Keywords: PLZT thick films; Sol-gel; Dielectric properties; Energy-storage properties; Electrocaloric effect